Sex Identification of in vitro Plants of Carica papaya L. MSXJ Hybrid through Molecular Markers (Agro Productividad, 2021)
Objective: To identify the sex of in vitro plants of papaya (Carica papaya L.) MSXJhybrid obtained via somatic organogenesis, through SCAR type molecular markers.Design/Methodology/Approach: Eight-month old MSXJ papaya hybrid plants in thefructification stage were collected in Cotaxtla, Veracruz, Mexico. They weresuperficially disinfected with abundant running water, detergent during 30 min, andthen alcohol at 70% was added for one minute, commercial chlorine at 30% for 30min, and they were rinsed with sterile distilled water; then the meristems werecultivated in MS medium and after 30 d a subculture was made. The DNA extractionwas made with the CTAB method, and the DNA PCR was done with the Deputy et al.(2002) method, and the primers T1, T12 and W11 were used.Results: The T1 primer was the positive control and the T12 and W11 primersallowed the amplification of fragments that identify hermaphrodite, feminine and maleplants, while the T12 and W11 primers were specific for hermaphrodite plants.Study Limitations/Implications: It is required to standardize the method for it to beinexpensive.Findings/Conclusions: The sexuality of papaya plants can be differentiated until thestage of flowering, which is why the implementation of molecular markers wouldfacilitate plant selection if it is implemented at a large scale. Costs, maintenance timeand elimination of plants of unwanted sex are reduced this way.